Temporal Trends in Marine Litter at Three Stations of the HAUSGARTEN Observatory in the Arctic Deep Sea - Parga Martínez, Karla B.; Tekman, Mine B.; Bergmann, Melanie (Frontiers in Marine Science, 2020)
The deep sea is a major sink for debris; however, temporal changes and underlying mechanisms of litter accumulation on the seafloor remain unclear. Photographic surveys at the long-term ecological research (LTER) observatory HAUSGARTEN, in the eastern Fram Strait, have enabled the assessment of spatial and temporal variability of seafloor litter in the Arctic. Previous studies of time-series data (2002-2014) reported an increase in litter amounts from the northernmost and central stations. Here, we extended the analysis by three years until 2017 and included data from the southernmost station. A total of 16,157 images covering 60.5 km2 were analyzed, combined with previous studies, to determine litter density, type and size compositions. Moreover, the interaction of litter with epibenthic megafauna was evaluated. Indicators of local maritime traffic, fisheries activity and summer sea ice extent were examined as potential drivers. The mean annual litter density ranged between 813 ± 525 (SEM) and 6,717 ± 2,044 (SEM) items km-². Litter density clearly increased over time, and the northernmost station experienced the strongest increase. Plastics dominated at two of the stations (41%) whereas the northern station harbored mainly glass (41%). Small-sized items accounted for 63%. The interaction with epibenthic fauna was frequent with sessile organisms. Litter densities correlated with fishing and tourism vessel presence, but no correlation was found with summer sea ice extent. This 15-year record of marine litter shows that even secluded Arctic ecosystems become increasingly subject to plastic pollution and that it will likely continue in the face of growing global plastic production rates and ineffective waste management policies.